The First International Conference on &Amp;ldquo;Green” Polymer Materials 2020 2020
DOI: 10.3390/cgpm2020-07190
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Modified Bitumen Using EPS Beads for Green and Sustainable Development of Polymer-Based Asphalt Mixtures

Abstract: The increasing costs of virgin content, decreasing resources, and growing plastic waste have shifted the research momentum towards green and sustainable road pavements. Hence, in recent years, various researchers have worked on the utilization of different types of plastic wastes in asphalt concrete by replacing it with binder content. Under this premise, this study examines the effect of expanded polystyrene beads (EPS) as a replacement to the binder at seven different dosages ranging from 5% to 50%. The bitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…ey also concluded that the softening value of EPS-modified bitumen improved as the percentage of EPS content increased, indicating that using EPS-modified asphalt for the construction of flexible pavement in hot temperature conditions would be the best alternative [19].…”
Section: Effect Of Waste Eps On the Physical Properties Of Asphaltmentioning
confidence: 95%
See 2 more Smart Citations
“…ey also concluded that the softening value of EPS-modified bitumen improved as the percentage of EPS content increased, indicating that using EPS-modified asphalt for the construction of flexible pavement in hot temperature conditions would be the best alternative [19].…”
Section: Effect Of Waste Eps On the Physical Properties Of Asphaltmentioning
confidence: 95%
“…In a prior investigation, the authors discovered that when the penetration and softening point of EPSmodified asphalt increased, the ductility and flow values decreased. According to Marshall stability test results, the stability of AC-containing EPS was increased with varying percentages of EPS substitution up to 40%, but after that, a little decline in their stability values was noted at 50% replacement [19].…”
Section: Effect Of Eps On the Marshall Properties Of Asphaltmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to prepare the WS modified bitumen, the recent literature linked with the polymer modification processes were analyzed , Lin t. al. 2019, Anwar et al, 2020, Yıldız et al 2021). In the light of the cited studies, production processes of WS modified bitumen were determined.…”
Section: Production Of Ws Modified Bitumenmentioning
confidence: 99%
“…The wet proc integrates plastic in the shape of flakes, pellets, or powder into warm bitumen whe polymer is processed from plastic wastes [22]. Plastics chosen for the wet method of require melting ranges just below the defined range, owing to standard blending temp atures between 160 to 170 °C [12,23]. Polymer modification process of mixing by both wet and dry method [24].…”
Section: Introductionmentioning
confidence: 99%